2005
DOI: 10.1002/ana.20528
|View full text |Cite
|
Sign up to set email alerts
|

Depth of delayed cooling alters neuroprotection pattern after hypoxia‐ischemia

Abstract: Hypothermia after perinatal hypoxia-ischemia (HI) is neuroprotective; the precise brain temperature that provides optimal protection is unknown. To assess the pattern of brain injury with 3 different rectal temperatures, we randomized 42 newborn piglets: (Group i) sham-normothermia (38.5-39 degrees C); (Group ii) sham-33 degrees C; (Group iii) HI-normothermia; (Group iv) HI-35 degrees C; and (Group v) HI-33 degrees C. Groups iii through v were subjected to transient HI insult. Groups ii, iv, and v were cooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 74 publications
0
30
0
1
Order By: Relevance
“…This is in accord with the results of a few animal studies that focused on the effect of different HT target temperatures, although the temperature range varied among the studies (10,18 -19,22). Interestingly, another piglet study demonstrated a different HT temperature threshold between brain regions; whereas HT at 35°C and 33°C achieved better neuroprotection in the deep gray matter and in the cortical gray matter, respectively, (9). Whether this differential neuroprotection afforded by different HT target temperatures also applies to the smaller brain of the neonatal rat is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accord with the results of a few animal studies that focused on the effect of different HT target temperatures, although the temperature range varied among the studies (10,18 -19,22). Interestingly, another piglet study demonstrated a different HT temperature threshold between brain regions; whereas HT at 35°C and 33°C achieved better neuroprotection in the deep gray matter and in the cortical gray matter, respectively, (9). Whether this differential neuroprotection afforded by different HT target temperatures also applies to the smaller brain of the neonatal rat is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent short-term recovery studies in the piglet do suggest that the optimal degree of cooling is greater in the cortex than in the basal ganglia. 154 Supporting this experimental observation, in a recent case series, head cooling but not whole body cooling seemed to be associated with a reduction in the incidence of severe cortical lesions, 143 as examined by MRI. If this is correct, we would predict that the long-term followup of the CoolCap study may show a greater effect on cognitive ability.…”
Section: Is Head or Whole Body Cooling Better?mentioning
confidence: 75%
“…Cooling to 33 1C preserved more neurons in the cortex and hippocampus and cooling to 35 1C preserved more neurons in the deep nuclear gray matter. 38 Initial pilot studies in human newborns described reproducible approaches to both selective head and whole-body hypothermic therapy and confirmed the feasibility of such therapies. [39][40][41][42][43][44] Although these studies noted mild physiological changes in cardiovascular status and the potential for minor permutations in coagulation measurements, they showed that these changes were not clinically significant, that both methods of cooling were practical and that there were no major short-term consequences or complications to either method of cooling.…”
Section: Therapeutic Hypothermiamentioning
confidence: 91%